Shaming the Corporation: The Social Production of Targets and the Anti-Sweatshop Movement. (August 2014) - Bartley, Tim; Child, Curtis
As social movements co-evolve with changes in states and markets, it is crucial to examine how they make particular kinds of actors into focal points for the expression of grievances and the demand for rights. But researchers often bracket the question of why some kinds of organizations are more likely than others to become targets of social movement pressure. We theorize the "social production of targets" by social movements, rejecting a simple "reflection" model to focus on configurations of power and vulnerability that shape repertoires of contention. Empirically, we extend structural accounts of global commodity chains and cultural accounts of markets to analyze the production of targets in the case of the anti-sweatshop movement of the 1990s. Using a longitudinal, firm-level dataset and unique data on anti-sweatshop activism, we identify factors that attracted social movement pressure to particular companies. Firms' power and positions strongly shaped their likelihood of becoming targets of anti-sweatshop activism. But the likelihood of being a target also depended on the cultural organization of markets, which made some firms more "shamable" than others. Contrary to suggestions of an anti-globalization backlash, globalization on its own, and related predictions about protectionism, cannot explain the pattern of activism.